"Extractos vegetales es para el control de Meloidogyne en tomate (Lycopersicum esculentum) bajo condiciones controladas en la zona de Quevedo". - Palacios Cevallos, Jacinto Bernardo (2014)
This research was conducted at the Laboratory Finca from ¨La Maria¨ and the Laboratory of Microbiology, State Technical University of Quevedo, Quevedo City, Province of Los Ríos, located between 75 and 80 meters respectively, west longitude 79 º 28 '30'' south latitude and 01 ° 06', humid tropical climate, temperature 24.8 ° C, average annual rainfall of 2.252.2 mm, relative humidity 84%, and 894 hours annual sunshine hours / sun. The general objective of this research was to evaluate the efficacy of plant extracts in populations of Meloidogyne incognita on tomato. The specific objectives were: To study the efficacy of plant extracts on mortality of M. incognita, to determine the effect of plant extracts on the development of the nematode, and select the best extract for the control of M. incognita. Three factors were studied: Two extraction methods: (Infusion and cold water); 2 doses (10, 15 ml / plant using nematode infested soil); and 4 species of plants themselves in the humid tropics: Chaya (Cnidoscolus chayamansa), paradise tree (Melia azaderach L), Coriander (Eryngium foetidun L), verbena(Cymbopogon citratus), which was included the witness. Performed the analysis and interpretation of the results concludes extract more effective in reducing numbers of galls was coriander, causing rot in the nodule; controlling action observed nematodes by extracts of chaya and chinaberry. Verbena extract showed no adequate nematode control because the active ingredients of the plant were not effective in controlling nematodes. Coriander extract exerted greater effectiveness on the control of M. incognita. Not all research evaluated extracts effectively controlled the development of nematodes, due to the chemical nature of the same or defensive ability of nematodes and other environmental factors.